ADVANCED NUMERICAL AND EXPERIMENTAL STUDIES ON CI ENGINE EMISSIONS - GÜL, MEHMET ZAFER; YILMAZ, MUSTAFA (YILDIZ TECHNICAL UNIV, 2018)
In these studies, three important works examined to get ultra-low emission for a single cylinder diesel engine. The first study was performed for single fuel and compression ratio (CR), intake and exhaust valve timings, mass flow rate were optimized for a range of engine speed. Then for the same engine injection parameters such as start of injection (SOI), injector cone angle, and split injection structures were examined to get optimum parameters for the diesel engine. In CR studies, different combustion chambers were tested according to injector cone angles and fuel-wall interaction. In the second study, in addition to the above studies, dual fuel compressed biogas (CBG) and diesel combustion were analyzed under different engine loads both experimentally and computationally. Optimized single fuel diesel cases were compared with CBG + Diesel dual fuel cases which employed port injection for CBG fuel. In dual fuel engine applications, CBG fuel and air mixture is induced from intake port and this air-fuel mixture is ignited by pilot diesel fuel near top dead center (TDC). In dual fuel engine mode, exhaust emissions reduced considerably especially in NOx and particulate matter (PM) because of methane (CH4) rate and optimized engine parameters. The third study is focused on aftertreatment systems to minimize residual exhaust emissions. The emissions of the diesel engines consist of various harmful exhaust gases such as carbon monoxide (CO), particulate matter (PM), hydrocarbon (HC), and nitrogen oxides (NOx). Several technologies have been developed to reduce diesel emissions especially NOx reduction systems in last decades. The most promising NOx emission reduction technologies are exhaust gas recirculation (EGR) system to reduce peak cylinder temperature that reduces NOx form caused by combustion and active selective catalyst reduction (SCR) system using reducing agent such as urea-water-solution for exhaust aftertreatment system. In this study, computational fluid dynamic (CFD) methodology was developed with conjugate heat transfer, spray, deposit and chemical reaction modeling then emission prediction tool was developed based on the CFD results with deposit prediction mechanism. CFD and deposit results were correlated with image processing tool in flow test bench.
Keywords: Experimental Study; CI Engine; Emission; Optimization; Aftertreatment; EXHAUST EMISSIONS; SCR SYSTEMS